Multirate Formulation for Mismatch Sensitivity Analysis of Analog-to-Digital Converters That Utilize Parallel ΣΔ-Modulators. (15th November 2007) - Blad Blad, Anton Anton; Johansson Johansson, Håkan Håkan; Löwenborg Löwenborg, Per Per
Abstract : A general formulation based on multirate filterbank theory for analog-to-digital converters using parallel sigmadelta modulators in conjunction with modulation sequences is presented. The time-interleaved modulators (TIMs), Hadamard modulators (HMs), and frequency-band decomposition modulators (FBDMs) can be viewed as special cases of the proposed description. The usefulness of the formulation stems from its ability to analyze a system's sensitivity to aliasing due to channel mismatch and modulation sequence level errors. Both Nyquist-rate and oversampled systems are considered, and it is shown how the matching requirements between channels can be reduced for oversampled systems. The new formulation is useful also for the derivation of new modulation schemes, and an example is given of how it can be used in this context.